(untitled) (Journal of the College of Basic Education, 2023)
The word heretic means atheism, which is disbelief and atheism inwardly while pretending to be a believer.Persian word (1). We notice that the word heretic has been transferred to the Arabic language since the eraAl-Sasanian. (2) Al-Asma’i clarified the meaning of a heretic when he said: These people do not commit heretics exceptfor their ignorance of the Arabic language. This means that they did not understand the meanings of the Qur’anic verses and the hadiths of the Prophet.As it must be, and accordingly, heresy is confined to a limited class of thinkers and opinion-holders.It was found in the atmosphere in which the intellectual movement was active, especially in the cities of Basra and Kufa.And there are those who defined the meaning of heresy with the blame of deviant thinking and ijtihad from the path of righteousness (3).Baronen touched on the meaning of heresy, saying: The usual interpretation is that (heretic) is a Persian adjective.Its meaning is (source), i.e. the zand or the ancient commentaries (of the Avesta), which is the book of Zardasht (4).Manicheans were called heretics for their tendency to interpret the holy books of other religions.He explained it according to their opinions in a manner similar to the interpretation of the Ismailis later on (5).Kramer said that the heretics believed in dualism and that they followed the teachings of Mani.To the books of heretics in terms of contents, paper care and adornment (6). And heretics were not all of themManichaeism and the name of heretics, its meaning included all the owners of the Persian religions who appearIslam then came to include atheists and skeptics about religion (7).